2007
DOI: 10.1016/j.cub.2007.05.008
|View full text |Cite
|
Sign up to set email alerts
|

FT Protein Acts as a Long-Range Signal in Arabidopsis

Abstract: Plants are sessile organisms and must respond to changes in environmental conditions. Flowering time is a key developmental switch that is affected by both day length and temperature. Environmental cues are sensed by the leaves while the responses occur at the apex, requiring long-range communication within the plant. For many years it has been known that leaves exposed to light can trigger the floral transition of a darkened shoot, and grafting experiments demonstrated that the floral stimulus travels long di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
476
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 637 publications
(490 citation statements)
references
References 28 publications
(36 reference statements)
10
476
2
2
Order By: Relevance
“…In addition, the movement of FT protein is sufficient to trigger floral initiation, which suggests that the FT protein is a key part of the florigenic signaling pathway. 9,10,[20][21][22][23] Parallel proteomic analyses showed that FT protein is translocated through phloem sap, which is consistent with the notion that the florigen is transported along the phloem translocation stream. 24 Thus, FT protein is clearly part of the florigen.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, the movement of FT protein is sufficient to trigger floral initiation, which suggests that the FT protein is a key part of the florigenic signaling pathway. 9,10,[20][21][22][23] Parallel proteomic analyses showed that FT protein is translocated through phloem sap, which is consistent with the notion that the florigen is transported along the phloem translocation stream. 24 Thus, FT protein is clearly part of the florigen.…”
Section: Introductionsupporting
confidence: 81%
“…Arabidopsis transformants expressing NLS FT or 3XYFP:NLS in companion cells failed to complement the late flowering of ft mutants, which suggests that the movement of FT RNA is not sufficient to promote flowering. 20,21 However, because the movement of engineered FT RNA was not examined directly, the constructs used to interfere with the movement of FT protein may have affected the movement of FT RNA. In another experiment, the expression of an artificial miRNA against FT RNA in the apex did not affect floral initiation, which suggests that FT RNA in the apex is not necessary for flowering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in the SD plant rice, an FT homolog, Heading date3a, is activated when the CO homolog Heading date1 peaks after dusk in SDs (Hayama et al, 2003). After the activation of FT expression, the FT protein moves through the phloem to the shoot apex (Corbesier et al, 2007;Jaeger and Wigge, 2007;Tamaki et al, 2007), where 14-3-3 proteins bridge its interaction with a bZIP transcription factor, FLOWERING LOCUS D (FD; Taoka et al, 2011). The FT/14-3-3/FD complex, in turn, induces flowering by up-regulating the floral meristem identity genes APETALA1 (AP1) and FRUITFULL (FUL; Abe et al, 2005;Wigge et al, 2005).…”
mentioning
confidence: 99%
“…There are some genes involved in flowering and among those genes, FLOWERING LOCUS T (FT) is a fl oral integrator that plays an important role in controlling fl owering time. Most recently, the nature of FT and its ortholog as fl origen, a mobile fl owering signal, has been proposed in tomato, rice, arabidopsis and cucurbits (Lifschitz, et al, 2006;Tamaki et al, 2007;Corbesier et al, 2007;Jaeger and Wigge, 2007;Mathieu et al, 2007;Lin et al, 2007;Notaguchi et al, 2008;Zeevart, 2008). At present, the isolation of FT gene in orchid (Oncidium Gower Ramsey) has been reported.…”
Section: Introductionmentioning
confidence: 99%